2023
DOI: 10.4236/ojog.2023.134064
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Therapeutic Aspects of Proctological Pathologies in Pregnant and Postpartum Women at the Reference Health Center of Commune IV of Bamako District

Abstract: Introduction: Painful proctological conditions that are far less pleasant can mar pregnancy and childbirth. In Mali, few studies have been carried out on proctological pathologies in pregnant women and in the postpartum period. Objective: To determine the frequency and identify the risk factors of anal pathologies during pregnancy and in the postpartum period in the obstetric gynecology department of the Centre de Santé de Référence de la comme IV du District de Bamako. Mali. Methods and Materials: Our observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
2
0
0
Order By: Relevance
“…Similar data was reported by Oumar et al [9]. However, Mariko et al [10] reported a comparatively younger age female population in their study [10].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar data was reported by Oumar et al [9]. However, Mariko et al [10] reported a comparatively younger age female population in their study [10].…”
Section: Discussionsupporting
confidence: 87%
“…A similar pattern of diagnosis was reported by Abramowitz et al [6] from France and Yadav et al [1] from Nepal. Mariko et al [10] from Mali also reported anal fissures and hemorrhoids as the commonest entities in their population [10]. Similar data is reported from Central Africa, Dakar, and India [11][12][13].…”
Section: Discussionsupporting
confidence: 61%